DETERMINATION OF WATER QUALITY INDEX OF POND EXTREMOZ-RN: TIME SERIES AND CORRELATION THE RAINFALL - Jeronimo, Carlos Enrique de Medeiros; Souza, Fladjule Rejane Soares (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707888 The water quality of the pond Extremoz-RN has been threatened in recent years due to the installation of an industrial complex in its vicinity, therefore, endangering the health of the population that uses it. This study aimed to provide summary information about water quality through an index, as well as relate the time series concerned with the influence of rainfall. Was adopted in this work the IQA as a support tool to the management of water resources, since it represents a good indicator of the trophic status of the lagoon. The use of IQA noted that water Lagoon Extremoz-RN fits in classes ranging from good to great. With the series was possible to visualize the variation of physical-chemical aspects of the stock and the rainfall as well as the negative correlation of the latter with the IQA, with coefficients of determination of the models on the order of 86%. The CCME WQI-used and most relevant parameters was consistent with therate-IQA NFS. Studies with this are essential to ensure water quality and establish systematicmonitoring in order to evaluate the evolution of the quality of the water body and know theirtendencies of variation.